How does a region react to different types of shocks? The case of a Brazilian T&C industrial region - Newton da Silva Miranda Junior; Valmir Emil Hoffmann; Renan Costa Filgueiras (Innovation & Management Review, 2023)
Purpose - This study aims to empirically investigate how an industrial region has reacted to different shocks - competitive, market and environmental - through its economic subsystems - its firms, workers and institutions - in a longitudinal perspective for the period 1985-2021. Design/methodology/approach - The authors used a mixed-method approach applied to a case study of the Brazilian T&C industrial region. The authors used two data sources and two stages for data collection. The first stage involved documentary research and the second in-depth interviews. The analysis of qualitative data took place in two stages. In the first, the authors applied content analysis, and in the second stage, the authors used the exploratory statistical technique of simple correspondence analysis and the categorical data. Findings - The results provide evidence that different types of shock provoke different reactions. However, the shock-reaction relationship is invariable over time. The authors observed proportionality in the size of the shock and the regional actors involved in the regional response - firms, workers and institutions. Originality/value - The authors went a step further, presenting empirical research on the shock-reaction relationship using the 'type of shock' as a variable. This paper provides a holistic understanding of the factors behind regional resilience through insights into the role that resources, structures, institutions and actors play in the regional response to distinct types of shocks, reaching four main conclusions.
Keywords: 650; Reactions; Regional economic subsystem; Regional resilience; Shocks